Aristotelian Meteorology in Syriac : Barhebraeus, Butyrum Sapientiae, Books of Mineralogy and Meteorology - Takahashi, Hidemi, (Aristoteles Semitico-Latinus ;, 2004)
This volume contains an edition, together with a translation and a commentary, of those parts relating to Aristotle's Meteorologica in Barhebraeus' Butyrum sapientiae (Cream of Wisdom) , the major philosophical work of the thirteenth-century Syriac prelate and polymath. Butyrum sapientiae , though based mainly on Ibn Sīnā's Kitāb al-šifāʾ (Book of Healing) , draws on a number of other sources. The detailed analysis of the text provided in this volume casts some important light on the manner in which Greek science and philosophy were transmitted in the Orient and as such will be of interest to scholars both of the Classical and Islamic world. The philological analysis of the text will be of interest to scholars of Syriac language and culture.